Evaluation of a simplified key for the identification of coagulasepositive Staphylococcus isolated from bovine mastitis - Geraldo Márcio da Costa (Acta Scientiarum. Biological Sciences, 2010)
Evaluation of a simplified key for the identification of coagulase-positive Staphylococcus isolated from bovine mastitis. Three hundred fourty four strains of coagulasepositive Staphylococcus (CPS), isolated from mastitis cases, underwent phenotypic and genotypic tests to evaluate the efficiency of a simplified key, based on phenotypic tests for the discrimination of these microorganisms. The tests consisted of amplification of the femA gene and hemolysis in blood agar, production of acetoin and fermentation of maltose, mannitol and trehalose. Strains that showed negative results in the amplification test of the femA gene or that were not identified as Staphylococcus aureus (S. aureus) by phenotypic tests were tested with the APISTAPH kit (Biomériux-France), for precise identification of species. Phenotypic tests revealed 338 strains (98.25%) as S. aureus, three strains (0.86%) as Staphylococcus hyicus, and three microorganisms (0.86%) as Staphylococcus intermedius. PCR demonstrated that 338 (98.25%) strains belonged to the S. aureus species, confirming the results for 336 strains from 338 identified, through a simplified phenotypic key. A high rate of correlation (98.83%) was verifeid between the results of genotypic and phenotypic tests for the identification of S. aureus, demonstrating the applicability of the proposed key, for the discrimination of this microorganism in CPS isolated from bovine mastitis.